Single-term Walsh series method for solving Volterra's population model - Sepehrian, Behnam (International Journal of Applied Mathematical Research, 2014)
Single-term Walsh series are developed to approximate the solution of the Volterra’s population model. Volterra’s model is a nonlinear integro-di?erential equation where the integral term represents the effect of toxin. Properties of Single-term Walsh series are presented and are utilized to reduce the computation of the Volterra’s population model to some algebraic equations. The method is computationally attractive, and applications are demonstrated through illustrative examples. A comparison is made with existing results. Keywords: Volterra’s population model, Numerical methods, STWS method.